The kaon electromagnetic form factor in the light-front formalism - Pereira, F. P. [UNESP]; De Melo, J. P.B.C. [UNESP]; Frederico, T.; Tomio, Lauro [UNESP] (My University, 2005)
Numerical calculations are performed and compared to the experimental data for the electromagnetic form factor of the kaon, extracted from both components of the electromagnetic current, J+ and J-, with a pseudo-scalar coupling of the quarks to the kaon. In the case of J+, there is no pair term contribution in the Drell-Yan frame (q+ = 0). However, for J-, the pair term contribution is different from zero and is necessary in order to preserve the rotational symmetry of the current. The free parameters are the quark masses and the regulator mass.